Motivation for Saving in Mutual Funds: Netnography Study on Bibit Instagram Posts - Ria, Reny Refitaningsih Peby (International Journal of Business, Law, and Education, 2023)
Developments in technology and information make it easier for Millennials and Z generations to access investment information and make investments through smartphones. Mutual fund investment can be the best alternative choice for beginners who want to start investing because mutual funds are investment products that are relatively easy to understand and accessible to anyone. In this regard, the use of digital platforms and applications makes the mutual fund investment transaction process faster and simpler, one of which is the Bibit application. The Bibit application is a platform used for mutual fund investment that provides mutual fund purchases with an affordable investment nominal.The purpose of this study is to analyze and describe the reasons Millennials and Z generations are motivated to save mutual funds in the Bibit application. This type of research uses netnography research with a qualitative approach. Data collection techniques by extracting comment content on Bibit Instagram posts. Meanwhile, data analysis used comment content analysis on Bibit Instagram posts and thematic analysis using Atlas.ti. The results showed that people's motivation to invest in the Bibit application was due to several factors including 1) self-control, 2) financial parenting, 3) financial management, 4) financial allocation, 6) investment, 7) profit, 8) addiction to saving, 9) financial freedom, 10) well-being. The results of this study can practically be used by future researchers to analyze online community interactions, especially mutual fund investment analysis in the Bibit application using the netnographic method for initial in-depth studies as a provision for conducting field research.